2021
DOI: 10.1021/acsami.1c18660
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Neutrophil Extracellular Traps Regulating Nanocarrier-Enhanced Inhibition of Malignant Tumor Growth and Distant Metastasis

Abstract: Tumor-associated neutrophil extracellular traps (NETs) play a critical role in promoting tumor growth and assisting tumor metastasis. Herein, a smart nanocarrier (designated as mP-NPs-DNase/PTX) based on regulating tumor-associated NETs has been developed, which consists of a paclitaxel (PTX) prodrug nanoparticle core and a poly-l-lysine (PLL) conjugated with the matrix metalloproteinase 9 (MMP-9)-cleavable Tat-peptide-coupled deoxyribonuclease I (DNase I) shell. After accumulating at the site of the tumor tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…First, the DNase I−MMP-9 cleavable peptide was synthesized as previously reported. 55 Briefly, the DNase I and sulfo-SMCC (mole ratio = 1:10) were reacted in protein storage solution (pH 7.4, including 0.4 M N-2-hydroxyethylpiperazine-N′-2-ethanesulfonic acid (HEPES) and 0.1 M NaCl) with gentle stirring at 4 °C for 2 h and allowed to react with 5-azidopentanoic acid−GPLGLAGQC polypeptide (MMP-9 responsive peptide; mole ratio = 1:1.2) at room temperature for another 4 h. The DNase I−MMP-9 cleavable peptide was obtained after dialysis using a 3.5 kDa cutoff membrane (Beyotime, Beijing, China) against PBS overnight at 4 °C and freeze-dried for further use. For comparison, the MMP-9 nonreactive conjugate was synthesized by replacing all L-type amino acids of polypeptide with D-type.…”
Section: Methodsmentioning
confidence: 99%
“…First, the DNase I−MMP-9 cleavable peptide was synthesized as previously reported. 55 Briefly, the DNase I and sulfo-SMCC (mole ratio = 1:10) were reacted in protein storage solution (pH 7.4, including 0.4 M N-2-hydroxyethylpiperazine-N′-2-ethanesulfonic acid (HEPES) and 0.1 M NaCl) with gentle stirring at 4 °C for 2 h and allowed to react with 5-azidopentanoic acid−GPLGLAGQC polypeptide (MMP-9 responsive peptide; mole ratio = 1:1.2) at room temperature for another 4 h. The DNase I−MMP-9 cleavable peptide was obtained after dialysis using a 3.5 kDa cutoff membrane (Beyotime, Beijing, China) against PBS overnight at 4 °C and freeze-dried for further use. For comparison, the MMP-9 nonreactive conjugate was synthesized by replacing all L-type amino acids of polypeptide with D-type.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been reported that neutrophils interact with tumor cells by using the same molecular machinery that induces EMT such as TGF-β, IL-8, CCl2, TNF-α, and IL-17a ( 61 , 100 ). Consistently, TGF-β pathways stimulate both EMT and the neutrophil pro-tumor phenotype (N2), which is likewise associated with therapy resistance ( 101 ). Emerging evidence suggests that neutrophils stimulate tumor progression through inducing EMT ( 60 , 109 , 110 ).…”
Section: Neutrophils In Cancer Progressionmentioning
confidence: 96%
“…Tumor metastasis is the major reason of huge number of cancer-associated deaths ( 97 ). In recent years, emerging studies have shown that NETs foster tumor metastasis in a wide range of cancer types ( 98 100 ), whereas NET depletion markedly decreases tumor metastasis ( 101 ). In line with these reports, in a more recent study published in Cancer Cell, Xiao et al.…”
Section: Neutrophils In Cancer Progressionmentioning
confidence: 99%
“…By combining CPP with drugs or other functional materials, it is possible to ‘switch on’ cellular uptake and drug delivery under MMP9-rich conditions. Yin et al ( 2021 ) developed an enzyme-cleavable targeted delivery system for the inhibition of malignant tumor growth designated as mP-NPs-DNase/PTX (Fig. 3 ) .…”
Section: Cpp-based Targeting Strategiesmentioning
confidence: 99%
“…3 Schematic representation of MMP9 responsive mP-NPs-DNase/PTX construction and NET regulation to enhance the inhibition of malignant tumor growth and distant metastasis. Reprinted with permission (Yin et al 2021 ) …”
Section: Cpp-based Targeting Strategiesmentioning
confidence: 99%